Mongooses (Urva auropunctata) as reservoir hosts of Leptospira species in the United States Virgin Islands, 2019–2020 - Cranford, Hannah M.; Browne, A. Springer; LeCount, Karen; Anderson, Tammy; Hamond, Camila; Schlater, Linda; Stuber, Tod; Burke-France, Valicia J.; Taylor, Marissa; Harrison, Cosme J.; Matias, Katia Y.; Medley, Alexandra; et al. (PLOS Neglected Tropical Diseases, 2021)
Author summary Leptospirosis is a zoonotic disease caused by bacteria of the genus Leptospira. To better understand local reservoirs and risk factors to humans and animals, during 2019–2020, the Virgin Islands Department of Health (VIDOH) investigated Leptospira spp. in association with the small Indian mongoose (Urva auropunctata, syn: Herpestes auropunctatus) across the three main islands of the United States Virgin Islands (USVI) (St. Croix, St. Thomas, and St. John). Mongoose blood and kidney samples were evaluated by laboratory testing: microscopic agglutination test, fluorescent antibody test (FAT), real-time polymerase chain reaction (lipl32 rt-PCR), and culture. Of 256 mongooses, 34% were exposed to Leptospira spp. To assess active infection in mongooses, kidney samples were examined resulting 5.8% (16/270) FAT-positive, 10% (27/274) culture-positive, and 12.4% (34/274) rt-PCR-positive. Validity was compared between test types showing higher positive predictive value for FAT and rt-PCR testing for predicting successful culture, the reference standard for diagnosis. Through the detection and isolation of Leptospira spp. in mongooses across the USVI, we identified mongooses as potential disease vectors to the local population and added to the limited data for the Caribbean region. Furthermore, a validity assessment of reference testing provides data to potentially inform future leptospirosis diagnostics.